Social Dynamics, Internet and the Survival of Broadcast Journalism in the 21st Century - Akpan, Uwem; Udoudom, Uduak; Nwokeocha, Ifeanyi; John, Innocent (Darul Yasin Al Sys, 2024)
This study looks at how broadcast news on TV and radio is changing in the 21st century because of the internet. The study used a theory that says technology shapes how we use media to see how social things affect how people consume news. Social media is changing how news is spread, and this paper is studying how regular people's content, online groups, and the quick spread of information play a big role. The paper looks at how the internet is changing traditional TV and radio news. The study is checking out challenges and chances that come with everything going digital, from online streaming to regular people reporting news. The paper looks at how old media and new online platforms work together and how they need to be flexible to survive. The study also looks at how people trust and believe in the news, especially with so much information online. Understanding how social things mix with online stories helps us get a better idea of what influences how the public sees and interacts with broadcast news. The study found that broadcast news needs to use social things and the internet to reach more people, but it also needs to keep its integrity and trustworthiness, especially in a time where false information can spread quickly. The study suggests that TV and radio stations should use online platforms to connect with people.